Letter - Thompson, J.
029-0164-001 Telegraphic Address: "WHOLESALE MANCHESTER" Telephone: BLACKFRIARS 1212. Extension No. Please Address Your Reply: Co-operative Wholesale Society Limited, Exporters, Buying and Shipping Agents, 1, Balloon Street, Manchester, 4. Cable Codes: A.B.C 6th and 7th editions; Western UNION 5 Letter; Bentley complete phrase; Bentley second phrase; A.1. Marconi, and private. Our Reference ST/HO.6809 Your Reference 26th April, 1937. The Trades Union Congress General Council, Transport House, Smith Street, LONDON, S.W.1. Dear Sirs, Further to correspondence relative to your order of the 5th April in respect of foodstuffs for Spain we now have pleasure in attaching hereto our invoice, which you will doubtless find in order. Up to the present we have not yet received stamped copy Bill of Lading from our loading brokers nor are the dock dues in our possession, but immediately we receive these charges and the Bill, we will write you further. Meanwhile, we remain, Yours faithfully, J. Thompson Export Department. EAB P. S. Enclosures - invoices amounts £1907. 4.7. 146 .15. 0. 106.19. 5. 2160 19 . 292/946/29/164